Being a good sport: players` uptake to coaches` joking in interviews for the youth national team - Kilger, M.; Aronsson, K. (Sports Coaching Review, 2020)
This paper draws on detailed analyses of authentic coach-athlete interviews during the final selection camp for the Swedish national youth team in hockey. The audio-recorded interviews between the coaches and the individual players (20 players and two national team coaches) covered various issues, involving both the individual players´ goal-setting and sports character, as displayed in his self-presentation during the interview. If the presumptive elite level player presented a vague or low goal or an overly humble self-presentation, this was contested by the coach through jokes, laughter or ironic teasing. Such conversational joking exchanges formed part of each coach´s toolkit for giving critical feedback to interview questions. In their uptake to the coaches playful corrections, the players were expected to engage in po-faced receipt or to laugh along. The selection involved character contests both on the ice rink and in the talk-in-interaction that formed part of the performance appraisal procedure.